Therapeutic potential of Abelmoschus manihot: mechanisms of action and clinical use in traditional Chinese medicine formulas - Xue, Chu; Ge, Haitao; Liu, Yaru; Zhao, Yan; Huang, Wenjie; Lu, Zhaowen; Ye, Qiuhui; Chen, Xiaoli; Cao, Zhengyu (Frontiers in Pharmacology, 2025)
Abelmoschus manihot (L.) Medicus (AM), commonly known as Huangshukui in China, is a traditional medicinal herb. Its flowers serve as the primary active component of Huangkui Capsule (HKC), which has demonstrated therapeutic potential in various conditions such as chronic kidney disease (CKD), inflammatory bowel disease (IBD), ischemic cardiac/cerebral injuries, hepatic injury, and diabetes mellitus. In order to reveal that AM has extensive clinical applications and significant development value, this paper collates the pharmacological effects of AM and the clinical data of traditional Chinese medicine (TCM) formulations containing AM. This review aims to systematically summarize the pharmacological effects and clinical applications of AM, with a focus on its underlying mechanisms—including immunomodulation, antifibrotic activity, metabolic regulation, intestinal flora modulation, organ protection, antioxidant effects, and analgesia. Although most clinical data currently center on HKC, this article also examines other TCM formulations containing AM, such as Jiahua Tablets, Chuangling Liquid, Huangkui Lianchang Decoction, Huangkui Siwu Formula, Yu Kui Qing, Qikui Granules, Huangshukui paste, and Er Huang Ointment. By consolidating current evidence on the pharmacology and clinical use of AM, this review highlights its broad therapeutic potential and promote further research and development of AM-based treatments.